Respuesta :
Solution:
- (x² + x – 12)(x² + 10x + 25)
- => (x⁴ + 10x³ + 25x²) + (x³ + 10x² + 25x) + (-12x² - 120x - 300)
- => x⁴ + 10x³ + 25x² + x³ + 10x² + 25x - 12x² - 120x - 300
- => x⁴ + (10x³ + x³) + (25x² + 10x² - 12x²) + (25x - 120x) - 300
- => x⁴ + (11x³) + (23x²) + (-95x) - 300
- => x⁴ + 11x³ + 23x² - 95x - 300
The only term that has a x-variable is "-95x".
The coefficient of x is -95.
[tex]\qquad \qquad\huge \underline{\boxed{\sf Answer}}[/tex]
let's evaluate ~
[tex]\qquad \sf \dashrightarrow \: ( {x}^{2} + x - 12)( {x}^{2} + 10x + 25)[/tex]
[tex]\qquad \sf \dashrightarrow \: {x}^{4} + 10 {x}^{3} + 25 {x}^{2} + {x}^{3} + 10 {x}^{2} + 25x - 12 {x}^{2} - 120x - 300[/tex]
[tex]\qquad \sf \dashrightarrow \: {x}^{4} + 11 {x}^{3} + 23 {x}^{2} - 95x - 300[/tex]
In the given expression we can clearly observe that the Coefficient of x is " -95 "